2018
DOI: 10.31393/morphology-journal-2018-24(3)-05
|View full text |Cite
|
Sign up to set email alerts
|

Features of total body sizes and anthropometric torso sizes in female volleyball players of mesomorphic somatotype

Abstract: Determination of constitutional parameters that are inherent in highly skilled athletes of a particular sport can serve as reliable predictive markers during sport selection. But the last time an indisputable fact is the somatotypological conditionality of individual sizes that characterize the external structure of the body, and the visceral structures of the organism. The purpose of the work is to establish differences in the anthropometric dimensions between young women volleyball players of high level of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It is so, because only in mesomorphs, which are characterized by a predominant development of the muscular component of the somatotype, a decrease in the chest girth during expiration and an increase in this case the parameters during inspiration indicates a great excursion of the chest. In our previous studies [20], it was also found, that mesomorphs female volleyball players, that there were a significantly larger parameters of the length, body mass, body surface area and another body sizes, than in young women in the same somatotype, who were not engaged in sport. Thus, we can conclude, that belonging to one constitutional type, does not provide a similarity of morphometric parameters of the chest in persons with different levels of physical activity.…”
Section: Discussionmentioning
confidence: 70%
“…It is so, because only in mesomorphs, which are characterized by a predominant development of the muscular component of the somatotype, a decrease in the chest girth during expiration and an increase in this case the parameters during inspiration indicates a great excursion of the chest. In our previous studies [20], it was also found, that mesomorphs female volleyball players, that there were a significantly larger parameters of the length, body mass, body surface area and another body sizes, than in young women in the same somatotype, who were not engaged in sport. Thus, we can conclude, that belonging to one constitutional type, does not provide a similarity of morphometric parameters of the chest in persons with different levels of physical activity.…”
Section: Discussionmentioning
confidence: 70%
“…The functional state of the central hemodynamics enables the most rapid detection of signs of overwork and overtraining. The peculiarities of the human body structure of the athletes influence the manning of the team, the choice of the tactical drawing of the game in defense and attack, on the definition of training techniques [9,10]. Until recently, the morphological and functional parameters of the athletes' body of sports games were evaluated on average values of parameters: football players, handball players, basketball players.…”
Section: Introductionmentioning
confidence: 99%